-18h+12=7-18h

Simple and best practice solution for -18h+12=7-18h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18h+12=7-18h equation:


Simplifying
-18h + 12 = 7 + -18h

Reorder the terms:
12 + -18h = 7 + -18h

Add '18h' to each side of the equation.
12 + -18h + 18h = 7 + -18h + 18h

Combine like terms: -18h + 18h = 0
12 + 0 = 7 + -18h + 18h
12 = 7 + -18h + 18h

Combine like terms: -18h + 18h = 0
12 = 7 + 0
12 = 7

Solving
12 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| s^2-26s=11 | | 4x^2=4/9 | | -13r-20-7r=-10+20 | | 8a-3=6a+17 | | 3(x+9)-7=x+10 | | -4p+6=1+p | | 4x/334+(678x+1)=4 | | -(8y-6)-(-7y-7)=4 | | 18y=18y-15 | | h^2-28h-47=0 | | v^2-8=0 | | -5n-32/3=-13/4(13/4n+1) | | 7z+8=2d-7 | | 529+474= | | (t+42)/3=(t+126)/7 | | 5x=12+2+6 | | 2x^1/3=x^-2/3 | | x=3(x+1)-2x | | -11.82+0.8k=2.9k+18.42 | | 2y-1=17 | | y=-2-5y+7y-2(4y-7) | | 1+3n=6n+4 | | 1/2+3/4z=-5/2 | | 15-12x=2x+13 | | 9x-4=7x-1 | | 9x-4+7x-1= | | E=ex | | k^2+4k+4=-7 | | 5(a-4)=6(a-7) | | -[8x+(3x+8)]=1-(3x+3) | | -0.64-6.7u=-6.7u | | 8-3[5-(4y-8)]=0 |

Equations solver categories